Zhodnocení finanční situace podniku a návrhy na zlepšení - Říhová, Lada (Vysoké učení technické v Brně. Fakulta podnikatelská, 2008)
Diplomová práce analyzuje finanční situaci podnikatelského subjektu. Obsahuje analýzu poměrových ukazatelů a vybrané bankrotní modely, na základě kterých byla navrhnuta opatření vedoucí k zajištění stability a perspektivy podnikatelských aktivit.

The Master´s thesis analyses financial situation of the entrepreneurial entity. It includes analysis of financial ratios and selected bankruptcy models, based on whose steps leading to assurance of stability and prosperity of entrepreneurial activities were proposed.
Evaluation of Company Financial Performance and Proposals of Improvement
Keywords: analyzovat; bankrotní modely; zajištění; stabilita; podnikatelské aktivity; analyse; bankruptcy models; assurance; stability; entrepreneurial activities